1995
DOI: 10.1007/bf01707410
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prostacyclin on gastric intramucosal pH in patients with septic shock

Abstract: Infusing PGI2 in patients with septic shock increases pHi probably by enhancing blood flow to the splanchnic bed and thereby improves splanchnic oxygenation even when conventional resuscitation goals have been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…We considered 10 mmHg as the lowest difference between a normal PCO 2 gap (1 1 mmHg) and an elevated PCO 2 gap. In septic shock patients the PCO 2 gap is generally slightly elevated (from 12 to 20 mmHg) [9,24,25,26,27] yet still lower than the 25 mmHg which Schlichtig et al fix as the highest value of the PCO 2 gap compatible with aerobic metabolism [28]. It is therefore difficult to correlate an increase in the PCO 2 gap and ischemic gastric mucosa.…”
Section: Na Nsmentioning
confidence: 75%
“…We considered 10 mmHg as the lowest difference between a normal PCO 2 gap (1 1 mmHg) and an elevated PCO 2 gap. In septic shock patients the PCO 2 gap is generally slightly elevated (from 12 to 20 mmHg) [9,24,25,26,27] yet still lower than the 25 mmHg which Schlichtig et al fix as the highest value of the PCO 2 gap compatible with aerobic metabolism [28]. It is therefore difficult to correlate an increase in the PCO 2 gap and ischemic gastric mucosa.…”
Section: Na Nsmentioning
confidence: 75%
“…Other studies have focused on the effects of PG1 2 on the splanchnic region as assessed by gastric tonometry but these studies have produced conflicting results. One study in septic patients showed increased pHi and increased overall oxygen delivery [69] whereas another study found increased pHi without a change in oxygen transport variables after PGI 2 was given [70]. A major drawback in PGI 2 therapy in all these studies was an increased venous admixture and a dose-dependent lowering of the systemic blood pressure.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In this context, ongoing treatment with continuous intravenous noradrenaline may have assumed particular importance: first, treatment with noradrenaline seems to be associated with particular perturbations of hepatic perfusion and VO 2 spl [30]; second, the well-known thermogenic effect of noradrenaline in the splanchnic region [22] may have blunted an additional effect of dobutamine; and, finally, reduced b -adrenergic receptor responsiveness due to this treatment may have attenuated the efficacy of dobutamine [31,32]. Since alterations in b -receptor responsiveness also arise without exogenous catecholamine administration [31], such differences may also explain the inconsistent findings of Ruokonen et al as well as the variable influence of dobutamine on tonometric intramucosal pH in different studies [11,12,14,33].…”
Section: J Vogt H Reinelt P Radermachermentioning
confidence: 52%